Jambi Community Trust in Local Government; Mandatory Coronavirus-19 Vaccination - Yulius Yohanes; Elyta Elyta; Eka Apriyani; Ulung Pribadi; Akhdiva Elfi Istiqoh; Asriadi Asriadi (Universitas Padjadjaran, 2024)
This study analyses the Jambi people's trust in the local government regarding the obligation to vaccinate against Covid-19. To make it easier for the public to access and complete voluntary questionnaires, one hundred respondents completed a survey using a Google form. This study used a quantitative method with four independent variables that influence perceptions of responsiveness, perceptions of accountability, perceptions of transparency, and perceptions of usability. The findings of this study indicate that perceived responsiveness and transparency have a positive and significant influence in encouraging Jambi people's trust. The achievement of p-value perceived responsiveness (0.026) and perceived transparency (0.014) means that the results are supported and accepted. Meanwhile, the variables perceived accountability (0.284), and perceived usefulness (0.078) indicate that these two variables have no significant effect and are rejected. Local governments need to pay attention to perceptions of responsiveness and perceptions of transparency so that the mandatory COVID-19 vaccination policy can work and be well received by the community and does not become a paradox of public administration.